Educational Financing Management and Its Impact on Educational Quality: - Sette, Landro; Ismanto, Bambang (Edusight International Journal of Multidisciplinary Studies, 2024)
This study discusses the management of educational financing and its impact on the quality of education. The quality of education is the main goal in educational management, and appropriate financing is a key factor in achieving it. This study used a literature study method to analyze educational financing standards, including investment, personnel, and operational costs. In addition, this study highlights the importance of transparency and accountability in fund management, as well as the role of financing as a driving force for other educational standards. The findings show that good fund management, in accordance with the principles of accountability, can increase the credibility of educational institutions and ultimately have a positive impact on the quality of education.